Nusantara-Islamic Pedagogy in a Transnational Context: Teaching Classical Islamic Texts to Indonesian Diaspora Learners in Kuala Lumpur - Mahmudah, Novy Nur; Auliya Ridwan; Haidir Ali (Tebuireng: Journal of Islamic Studies and Society, 2025)
This study explores the implementation of Nusantara-Islamic Pedagogy (NIP) in teaching Islamic Education (PAI) using the classical text Mabādi’ al-Fiqh at the Indonesian School Kuala Lumpur (SIKL). NIP integrates traditional pesantren methods—such as sorogan, bandongan, halaqah, and uswah hasanah (teacher exemplary)—into the context of diaspora students facing linguistic, cultural, and technological challenges. Employing a qualitative case study with a participatory approach, the researcher acted as an instructor for grades V and VI, gathering data through classroom observations, in-depth interviews, and teaching reflections. The findings reveal that NIP fosters a contextual, inclusive, and relevant learning environment for diaspora learners. Synergizing classical methods with innovative strategies including visual media, microlearning, and gamification significantly enhanced students’ practical understanding of Islamic teachings. However, challenges remain, particularly limited proficiency in unvocalized Arabic texts (Indonesian: kitab gundul) and instructional time constraints. This study recommends enhancing teachers’ cross-cultural competencies and developing flexible curricula to ensure the sustainable application of NIP in international school environments.